The Gateway to Computer Science Excellence
First time here? Checkout the FAQ!
x
0 votes
120 views
Using Armstrong’s axioms of functional dependency derive the following rules:

$\{ x \rightarrow y, \: z \subset y \} \mid= x \rightarrow z$

(Note: $x \rightarrow y$ denotes $y$ is functionally dependent on $x$, $z \subseteq y$ denotes $z$ is subset of $y$, and $\mid =$ means derives).
asked in Databases by Veteran (97.7k points) | 120 views

1 Answer

+2 votes
Best answer
$\because z\subset y$, Trivially $y\rightarrow z $ . Now by transitivity, $x \rightarrow y, y \rightarrow z \implies x \rightarrow z$
answered by Active (2.1k points)
selected by

Related questions

Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true
49,814 questions
54,518 answers
188,351 comments
75,287 users